2000
DOI: 10.1177/104063870001200610
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Liver Lesions Caused by Experimental Infection with Piscirickettsia Salmonis in Juvenile Atlantic Salmon, Salmo Salar L

Abstract: Abstract. Piscirickettsia salmonis, the etiologic agent of salmonid rickettsial septicemia (SRS), or piscirickettsiosis, causes substantial economic losses to the salmon industry. The pathogenesis of the disease has not been fully characterized. The aim of this study is to describe the hepatic lesions associated with experimental P. salmonis infection in Atlantic salmon juveniles. Fish were maintained in fresh water and inoculated intraperitoneally (IP), orally, or on the gill surface with P. salmonis. A group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
4
13
0
2
Order By: Relevance
“…Wang et al [18] showed that catfish susceptible to Edwardsiella ictaluri presented increased acute phase responses, but the disease itself, could not be controlled. Macrophages, monocyte-like cells and the endothelium are important for explaining the body dynamics and containment of Piscirickettsia salmonis [19,20]. Our results show that the monocytemacrophage system associated gene LysC was up regulated in resistant fish, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 95%
“…Wang et al [18] showed that catfish susceptible to Edwardsiella ictaluri presented increased acute phase responses, but the disease itself, could not be controlled. Macrophages, monocyte-like cells and the endothelium are important for explaining the body dynamics and containment of Piscirickettsia salmonis [19,20]. Our results show that the monocytemacrophage system associated gene LysC was up regulated in resistant fish, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 95%
“…All macro‐ and microscopic pathological changes observed in this study were consistent with those previously described after both natural and experimental outbreaks (Almendras, Fuentealba, Markham, & Speare, ; Evensen, ; Fryer & Hedrick, ; Meza et al, ; OIE, ).…”
Section: Discussionsupporting
confidence: 91%
“…The systemic nature of the infection has been demonstrated by the presence of infected macrophages in blood smears from infected fish (Cvitanich et al, 1991). Almendras, Fuentealba, Markham, and Speare (2000) described the development of liver lesions in Atlantic salmon infected with P. salmonis through intraperitoneal (i.p. ), oral and gill infections.…”
mentioning
confidence: 99%